A BODIPY‐Based Water‐Soluble Fluorescent Probe for Mitochondria Targeting. Issue 16 (23rd May 2016) - Sui, Binglin; Tang, Simon; Woodward, Adam W.; Kim, Bosung; Belfield, Kevin D.
Abstract : A water‐soluble fluorescent mitochondrial targeting probe is reported. The probe bears a BODIPY‐based fluorophore, two triphenylphosphonium (TPP) groups as mitochondrial targeting moieties, and two PEG groups to increase water solubility and enhance biocompatibility. As a mitochondria‐selective fluorescent probe, the new BODIPY derivative exhibited many desirable properties, such as water solubility, high fluorescence quantum yield, solvent independent photophysical properties, pH insensitivity, good photostability, low cytotoxicity, and excellent mitochondrial targeting ability. Fluorescence microscopy colocalization experiments demonstrated the ability of this new probe to target mitochondria within living cells for bioimaging. Abstract : A new fluorescent probe composed of three moieties, a BODIPY platform functioning as the fluorophore, two TPP groups serving as mitochondria targeting moieties, and two PEG groups to increase water solubility and hinder undesired intramolecular rotations, was designed and synthesized for mitochondria targeting and imaging in living cells.